Carbon taxation and emission trading in Vietnam: insights from E-DSGE model - Ngoc Vu Thi Minh; Hang Trinh Thi Thu (Discover Sustainability)
Abstract This study develops the first Vietnam-specific Environmental Dynamic Stochastic General Equilibrium (E-DSGE) model, explicitly incorporating household heterogeneity, revenue redistribution rules, and carbon-pricing mechanisms. Using this novel framework, the research examines the macroeconomic and distributional impacts of Vietnam’s carbon taxation and emissions trading systems. The analysis focuses on how alternative revenue redistribution strategies influence economic performance and income equity, thereby providing policy insights for designing effective and equitable climate policy at the national level. The framework is calibrated for the period 2010–2022 and simulates four revenue-recycling scenarios where carbon revenues are recycled through labor tax reductions and production incentives. Results indicate that using carbon revenues to reduce labor taxes and support production can enhance economic efficiency and employment while achieving emission reduction goals. Under the welfare-maximising scheme aggregate CO2 emissions fall 19.8%, real GDP contracts by only 0.95%, and aggregate welfare declines by about 1.1% relative to the no-policy baseline. However, these policies may worsen income inequality without targeted support for low-income households. The choice of redistribution mechanism plays a crucial role in policy effectiveness. The model abstracts from household-level heterogeneity and sectoral differences, which could be explored in future research for more detailed policy insights. This study contributes a novel E-DSGE modeling approach to evaluate carbon pricing and revenue use, offering insights particularly relevant for developing economies facing the dual challenge of economic development and climate mitigation.